2016
DOI: 10.1016/j.psychres.2016.04.106
|View full text |Cite
|
Sign up to set email alerts
|

A strengths-based case management service for people with serious mental illness in Israel: A randomized controlled trial

Abstract: Case management services for people with serious mental illness are generally found to be effective, but controlled and randomized studies assessing such services are scarce. The aim of the present study was to assess the effectiveness of a new strengths-based case management (SBCM) service in Israel, using a randomized controlled approach. The sample consisted of 1276 individuals with serious mental illness, who consume psychiatric rehabilitation services (PRS) in the community, and were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 29 publications
0
29
0
2
Order By: Relevance
“…Quantitative evidence supporting ‘Recovery’ is emerging (Slade and Longden 2015 ). Studies have demonstrated the efficacy of case management emphasising recovery principles (Gelkopf et al 2016 ), service user managed services (Greenfield et al 2008 ), and specific ‘Recovery’ based interventions such as peer support and self-management (Davidson et al 2012 ; Cook et al 2012 ). However, how efforts to implement the recovery approach, in its totality, influence the service user experience is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative evidence supporting ‘Recovery’ is emerging (Slade and Longden 2015 ). Studies have demonstrated the efficacy of case management emphasising recovery principles (Gelkopf et al 2016 ), service user managed services (Greenfield et al 2008 ), and specific ‘Recovery’ based interventions such as peer support and self-management (Davidson et al 2012 ; Cook et al 2012 ). However, how efforts to implement the recovery approach, in its totality, influence the service user experience is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Only eight articles considered the three variables described by Goldman et al (1981) (psychiatric disorder, disability, and duration; Table 3). Another 16 studies defined SMI based on two variables: Gelkopf et al (2016), Hoffmann et al (2014), Levy-Frank et al (2011), Mueser et al (2014), Roe et al (2014), and Van Gestel-Timmermans et al (2012) argued that diagnosis and disability should be considered, whereas Bond et al (2001), Browne (1999), Cuffel et al (2002), Grocke et al (2014), Hulsbosch et al (2017), Huxley et al (2001), Jinnett et al (2001), Masa-Font et al (2015), McHugo et al (2004), and Puschner et al (2011) considered the diagnosis and duration relevant. In 15 studies, SMI was diagnosed solely on the basis of the diagnosed psychiatric disorder (Table 3), whereas Lehman et al (1997), Druss et al (2010), and Druss et al (2011) used different criteria to diagnose SMI depending on the psychiatric diagnosis (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Este aspeto corrobora o desenho deste programa de intervenção, que pretende ir ao encontro das necessidades das pessoas, à perceção da QdV e à satisfação com o suporte social avaliadas no início do programa de intervenção (M0), sendo os participantes do estudo ativos em todo o processo, promovendo, assim, também a sua autonomia A QdV é uma dimensão importante a avaliar porque, sendo multidimensional, também nos fornece dados para a intervenção dirigida às dimensões que apresentam scores mais baixos. Tendo como referência estudos efetuados no que se refere à avaliação da QdV da pessoa com doença mental (Gameiro et al, 2010, Macedo, 2013Figueira et al, 2010;Macedo, 2013;Vaz-Serra et al, 2010;Gameiro et al, 2008;Macedo, 2013), pareceu-nos importante que se desse um passo em frente, intervindo nesta dimensão e que os participantes alterassem positivamente, através do programa de intervenção, a perceção da QdV, facto que se veio a observar neste estudo. Relativamente à satisfação com o suporte social podemos afirmar que também se observou uma evolução positiva nos três momentos de avaliação, embora sem significado estatístico.…”
Section: Discussionunclassified
“…A QdV tem tido uma atenção especial por parte dos investigadores, embora esta atenção seja mais recente na saúde mental e psiquiatria. Apesar disso, já se observam alguns trabalhos envolvendo população diversa, como por exemplo, pessoas com diagnósticos psiquiátricos como depressão major (Gameiro, Carona, Silva e Canavarro., 2010, Macedo, 2013; doença bipolar (Figueira, Leitão e Gameiro, 2010;Macedo, 2013); a esquizofrenia (Vaz-Serra, 2010) ou; sintomatologia depressiva (Gameiro et al, 2008;Macedo, 2013). Ao longo da vida, o suporte social é construído através das relações estabelecidas com os membros da família, colegas de trabalho e pessoas da comunidade e, em caso de presença de necessidades especiais, de um membro resultante de profissões de ajuda (Cobb, 1976).…”
Section: Introductionunclassified